Al-Itqân Bimakhâriji Al-Hurûf Al-‘Arabiyah Wa ‘Alâqatuhu Bi Mahârah Al-Qirâ’ah Ladâ Talâmidzi Al-Madrasah Al-‘Āliyah Al-Muhammadiyah Lakitan - Marshy Delin Putri; Jarir NA HD; Hafni Bustami (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2021)
The main problem in this research is how the relationship between mastery of Arabic alphabet makhorij with reading skills of eleventh grade students in MA Muhammadiyah Lakitan Pesisir Selatan. This study aims to determine the results of students' Arabic makhorijl mastery, the results of students' reading skills, and the relationship between Arabic makhorij mastery and eleventh grade students' reading skills. This study is quantitative with the type of correlation. The results of this study are the first grades of the results makhorij abilities of eleventh grade students', the second grades of the results reading skills of eleventh grade students' and the third is the results of the relationship between makhorij abilities and reading skills the eleventh grade students' in  MA Muhammadiyah Lakitan